The Role of BPKPD in Determining the Price of Land Buying based on the Online BPHTB System - Rismawati, Annisa (Jurnal Konstatering, 2022)
This study aims to identify and analyze the role of the Regional Revenue and Financial Management Agency (BPKPD) in determining the price of buying and selling land and to find out and analyze the process of determining the price of buying and selling land by the BPKPD based on the Online Land and Building Rights Acquisition Fee (BPHTB) system. in Cirebon City. The approach method used in this research is the sociological juridical legal research method. The specification of this research uses descriptive analysis. The type of data used is primary data, namely data obtained directly through interviews and secondary data which includes books, journals, and applicable laws and regulations. The analytical method used is an inductive descriptive analysis which describes the data logically and then makes a conclusion.Keywords: Buying; BPHTB; Price; Selling.